Analysis Of Practices To Develop Students’ Reading Comprehension Skills - Berdiyeva Nilufar Ibadilullayevna (Academia One Publishing, 2025)
This article analyzes modern methodological approaches aimed at improving students' reading comprehension skills. Based on experimental research, the effectiveness of strategies such as graphic organizers, metacognitive techniques, question-and-answer sessions, and small group work was evaluated. The results showed that these methods significantly encourage deeper text analysis, promote independent thinking, and enhance reading efficiency. Practical recommendations based on teacher experience are also provided
Keywords: Reading comprehension; learner-centered approach